2020
DOI: 10.1590/1413-81232020253.17212018
|View full text |Cite
|
Sign up to set email alerts
|

Acesso e uso de serviços de Fonoaudiologia em Porto Alegre, Brasil: estudo populacional

Abstract: Resumo O objetivo deste artigo é estimar a prevalência de acesso e uso dos serviços de Fonoaudiologia e identificar as variáveis associadas ao acesso. Estudo transversal de base populacional. A amostra foi composta de indivíduos adultos residentes em Porto Alegre/RS. Os dados foram coletados a partir de um instrumento construído com domínios de questionários de pesquisas nacionais, com um módulo sobre Fonoaudiologia. O desfecho estudado foi o acesso ao fonoaudiólogo. Regressão de Poisson com variância robusta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…1,3 Evasion in this phase demonstrates a rupture in the continuity of care and reflects the obstacles of the Network of Care for People with Disabilities, which are the waiting lists for health services, flaws in the regulatory system, the low supply of care and specialist professionals such as speech therapists and the concentration of services in more urban areas. 9,[24][25][26] The HHS does not have an active search program for the completion of the hearing assessment, which could help the early diagnosis of hearing loss and enable the child to remain in the Health Care Network, being valid for cases of diagnosis and monitoring auditory.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Evasion in this phase demonstrates a rupture in the continuity of care and reflects the obstacles of the Network of Care for People with Disabilities, which are the waiting lists for health services, flaws in the regulatory system, the low supply of care and specialist professionals such as speech therapists and the concentration of services in more urban areas. 9,[24][25][26] The HHS does not have an active search program for the completion of the hearing assessment, which could help the early diagnosis of hearing loss and enable the child to remain in the Health Care Network, being valid for cases of diagnosis and monitoring auditory.…”
Section: Discussionmentioning
confidence: 99%
“…Para consolidação efetiva da Fonoaudiologia no SUS, é fundamental observar e estudar os indicadores em saúde relacionados à saúde fonoaudiológica (5,25) . Os dados epidemiológicos justificam as ações fonoaudiológicas no âmbito coletivo, além de caracterizar a população que demanda o atendimento especializado do profissional fonoaudiólogo (5,9) .…”
Section: Discussionunclassified
“…Embora os dados sejam escassos, sabe-se que estudos estimaram prevalência de, aproximadamente, 30,8% de alterações fonoaudiológicas na população adulta brasileira (4) . Sabe-se que a espera por atendimento fonoaudiológico no SUS é prolongada e há pouca rotatividade de usuários, em virtude de tratamentos mais longos (5,6) . Além disso, a oferta de atendimento fonoaudiológico é limitada e existem obstáculos, principalmente relacionados à regulação e à falta de critérios para encaminhamentos aos serviços, o que dificulta o acesso e a continuidade da atenção fonoaudiológica, independentemente do nível de complexidade (2) .…”
Section: Introductionunclassified
“…For the effective consolidation of speech-language pathology and audiology in SUS services, indicators related to speechlanguage and hearing health must be studied (5,25) . Epidemiological data can justify speech-language and hearing policies at the collective level, in addition to characterizing the population that needs specialized care from speech-language and hearing therapists (5,9) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding speech-language and hearing disorders among the Brazilian adult population (4) , although data are scarce, studies have reported a prevalence of approximately 30.8%. It is common knowledge that the wait for SLHT through SUS is protracted and patient turnover is slow due to longer treatments (5,6) . In addition, SLHT services are limited and difficult to access, mainly because of poor regulation and referral criteria which make it difficult to begin and continue SLHT, regardless of the level of complexity (2) .…”
Section: Introductionmentioning
confidence: 99%